2019
DOI: 10.1111/sms.13522
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, beliefs, and behavior toward shoulder injury prevention in elite handball: Fertile ground for implementation

Abstract: We aimed to examine attitudes, beliefs, and current behavior toward risk factors and prevention of shoulder injuries, and to investigate the application of an exercise program during a cluster‐randomized controlled trial aiming to prevent shoulder injuries in elite handball. All captains and coaches of 44 elite handball teams (22 male and 22 female) constituting the intervention (21 teams) and control arm (n = 23 teams) in the trial were invited to take part in a survey. A questionnaire, based on the Reach, Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…Although the OSTRC shoulder injury prevention program is an effective program, 9 player compliance remains a challenge, as the program is time consuming 17 . This study demonstrated that the program does not affect the risk factors, ER strength, and IR ROM.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Although the OSTRC shoulder injury prevention program is an effective program, 9 player compliance remains a challenge, as the program is time consuming 17 . This study demonstrated that the program does not affect the risk factors, ER strength, and IR ROM.…”
Section: Resultsmentioning
confidence: 74%
“…The study demonstrated 28% lower risk of shoulder problems in the intervention group than in the control group. However, despite of the effect on shoulder problems, only 24% of the athletes and 28% of the coaches reported that they would continue using the program 17 . Their main concern was that the program was too time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs études qualitatives [17] , [18] ont montré que les sportifs croyaient que les programmes de prévention des blessures pouvaient diminuer l’incidence de celles-ci. Notre travail confirme cette tendance puisque tous les athlètes étaient d’accord avec cette proposition « Je pense qu’un programme de prévention des blessures diminuerait la survenue de celles-ci ».…”
Section: Discussionunclassified
“…À partir de la littérature basée sur l’analyse du ressenti des sportifs vis-à-vis des blessures, nous avons élaboré notre propre questionnaire [17] , [18] , [19] , [20] . Deux médecins du sport, un chercheur en psychologie du sport et de la santé, un entraîneur d’athlétisme et une psychologue ont participé à sa réalisation.…”
Section: Matériel Et Méthodesunclassified
See 1 more Smart Citation